Massage therapy in the treatment of lymphedema. - Bernas, M.
Lymphedema (LE) afflicts hundreds of millions people worldwide. Manual lymph drainage, a specialized form of massage therapy, is an integral component - along with compression bandaging (CB) - of combined physical therapy (CPT), an internationally recommended optimal treatment. Experimental data from a rat model of obstructive LE suggests that massage alone can reduce LE volume as effectively as CB and CPT, at least early in the pathologic process. In a preliminary retrospective clinical study, it was also found that massage alone in a cohort of patients with mild stable upper-limb LE was as effective as CPT in volume reduction (massage 80.6 ± 0.2% decrease compared to CPT 72.6 ± 0.2%, mean ± standard deviation, not significant). These initial studies lay the groundwork and evidence-based rationale for the design and implementation of the expanded, prospective randomized clinical trial of massage alone in various types and stages of LE in children and adults.
Keywords: Combined physical therapy; Compression bandaging; Lymphedema treatment; Manual lymph drainage; Massage therapy; Mild stable upper-limb lymphedema; Volume reduction